PREDIKSI NIAT PENGGUNAAN APLIKASI DAN PERMAINAN DARING FREEMIUM VERSI BERBAYAR DENGAN MENGGUNAKAN MODEL TPB - Harmanda Berima Putra; Nungki Pradita; Kristina Anindita Hayuningtias (Unib Press Universitas Bengkulu, 2020)
This study investigates how the Theory of Planned Behavior determines the customer intention to use the freemium paid version of online apps and games. Data were collected using an online questionnaire which is distributed to 189 students at several universities in Indonesia. Data were then analysed using structural equation modelling by Amos. The results show that the subjective norm has a positive effect on perceived behavioral control and attitude. Perceived behavioral control has a positive effect on intention. In addition, attitude did not have a significant effect on intention to use the freemium paid version of online apps and games. Keywords: Freemium; Game Online; Intention; Theory Planned Behavior